Top Quark Physics at Hadron Colliders - Quadt, Arnulf (Advances in the Physics of Particles and Nuclei, 2007)
More than ten years after its discovery, still relatively little is known about the top quark, the heaviest known elementary particle. The present extensive survey summarizes and reviews top-quark physics based on the precision measurements at the Fermilab Tevatron Collider, as well as the sensitivity of these experiments to new physics. Finally, an outlook on top quark physics at the Large Hadron Collider is given.